Productive teacher job satisfaction: Disentangling organizational climate, facility management, and organizational citizenship behavior - Soparidah Soparidah; R. Madhakomala; Ivan Hanafi (Institute of Advanced Engineering and Science, 2021)
Productive teachers are teachers who teach vocational subjects. A productive teacher has complex characteristics and professional requirements so that job satisfaction must be considered. The research objective was to analyze the direct effect of organizational climate, management of facilities and infrastructure, organizational citizenship behavior on the job satisfaction of productive teachers. The research employed a quantitative approach with a survey method. The research sample was conducted at 46 private vocational high schools with a total of 270 productive teachers in East Jakarta, Indonesia. Data was analyze using path analysis. The results showed that there is no direct influence of organizational climate on job satisfaction of productive teachers; there is no direct effect of facility and infrastructure management on job satisfaction of productive teachers; there is a direct influence of organizational citizenship behavior on job satisfaction of productive teachers.